Antibacterial, breathable, hydrophobic and self-cleaning bionic fiber tactile sensor and preparation method and application thereof
By using a fiber substrate in the flexible sensor to integrate with ZIF-67, Ag NWs and superhydrophobic stearic acid STA, combined with a high-stability ionic liquid electrolyte layer, the comfort and safety of the sensor during long-term wear is solved, and superhydrophobicity, self-cleaning, breathability and antibacteriality are achieved, and the performance and application range of the sensor are improved.
Patent Information
- Application Number
- CN202411983519.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-10-23
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-31
AI Technical Summary
Existing flexible sensors are prone to skin itching and inflammation when worn for a long time, and there are inbiocompatible materials and toxic chemicals, which affect the comfort and safety of wearing.
The fiber is used as the substrate to integrate with ZIF-67, Ag NWs with high conductivity and antibacterial properties, and superhydrophobic stearic acid STA to form an electrode layer; an electrolyte layer with different microstructures on both sides is prepared using a mixed solution of ionic liquid rich in anions and cations and high stability, so as to achieve superhydrophobicity, self-cleaning, breathability and antibacteriality.
It realizes the superhydrophobicity and self-cleaning of the sensor, extends the service life and expands the application range; it has good breathability and antibacterial properties, improves wear comfort and safety, and improves sensitivity and detection range.
Smart Images

Figure CN119779522A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of flexible sensors, and in particular relates to an antibacterial, breathable, hydrophobic and self-cleaning bionic fiber tactile sensor, and a preparation method and application thereof. Background Art
[0002] The rapid development of information technology and the Internet of Things has increased the demand for smart sensing devices. Flexible sensors similar to human skin have been widely used due to their ability to interact with the environment, collaborate with robots, and monitor health. However, most of the reported sensors are based on solid or impermeable polymer substrates, and long-term wear can cause itching, inflammation, and other problems on the skin, seriously affecting the wearing comfort. In addition, the presence of non-biocompatible materials and residual toxic chemicals in the sensors may cause serious damage to the skin during long-term use. Therefore, it is urgent to prepare a flexible sensor that is both breathable and biocompatible to meet the stringent requirements of human motion detection and implantable electronic devices. Fiber-based tactile sensors have good breathability and easy integration with smart clothing. However, the fiber substrate has natural water absorption, which makes the designed sensor vulnerable to sweat or water after long-term wear. Therefore, it is urgent to develop a hydrophobic sensor, which is crucial to extend its service life and expand its application range. Therefore, it is crucial to develop a fiber-based sensor with antibacterial, breathable, and hydrophobic properties to obtain comfortable wearable motion detection for humans. Summary of the invention
[0003] In view of this, in order to solve the above technical problems, the present invention proposes an antibacterial, breathable, hydrophobic, self-cleaning bionic fiber tactile sensor, and also provides its preparation method and application. The electrode layer is obtained by using fiber as a substrate and integrating with ZIF-67 with a highly stable structure, Ag NWs with high conductivity and antibacterial properties, and superhydrophobic stearic acid STA; an electrolyte layer with different microstructures on both sides is obtained by using a mixed solution of ionic liquids rich in anions and cations and high stability, one side of which is a through-hole and protrusion combined microstructure, and the other side is an octopus-like sucker structure; the bionic fiber tactile sensor has superhydrophobicity, can resist the penetration of the solution, and has self-cleaning properties, reducing the damage to the sensor surface material, and has good air permeability, allowing the transmission of air / water, and has antibacterial properties, maintaining the balance of the skin system, and has good sensitivity and detection range.
[0004] To achieve the above object, the technical solution of the present invention is achieved as follows:
[0005] The present invention provides an antibacterial, breathable, hydrophobic, self-cleaning bionic fiber tactile sensor, comprising:
[0006] ZIF-67 / Ag NWs / STA fiber electrode layer, wherein the ZIF-67 / Ag NWs / STA fiber electrode layer is based on fiber, loaded with ZIF-67, coated with Ag NWs on both sides, and then hydrophobically modified on one side by STA;
[0007] An IL / PVDF electrolyte layer, wherein the IL / PVDF electrolyte layer is loaded with ions, one side of the IL / PVDF electrolyte layer is a through-hole and protrusion combination microstructure, and the other side is an octopus suction cup-like structure;
[0008] There are two ZIF-67 / Ag NWs / STA fiber electrode layers, which are respectively attached to two surfaces of the IL / PVDF electrolyte layer, and the non-hydrophobic modified surface of the ZIF-67 / Ag NWs / STA fiber electrode layer faces the IL / PVDF electrolyte layer.
[0009] In some preferred embodiments of the bionic fiber tactile sensor of the present invention, the ZIF-67 / Ag NWs / STA fiber electrode layer is prepared by loading ZIF-67 on the fiber by an in-situ growth method in a mixed solution of 2-methylimidazole, cobalt nitrate hexahydrate and methanol, coating Ag NWs solution on both sides, drying, and then spraying a hydrophobic STA solution on one side and drying.
[0010] In some preferred embodiments of the bionic fiber tactile sensor of the present invention, in the mixed solution of 2-methylimidazole, cobalt nitrate hexahydrate and methanol, the molar ratio of 2-methylimidazole to cobalt nitrate hexahydrate is 2-3:5-15, and the molar concentration of 2-methylimidazole in methanol is 0.25-1 mol / l.
[0011] In some preferred embodiments of the bionic fiber tactile sensor of the present invention, the concentration of the Ag NWs solution is 4-7 mg / mL
[0012] In some preferred embodiments of the bionic fiber tactile sensor of the present invention, the mass ratio of STA to water in the hydrophobic STA solution is 1:100-125.
[0013] In some preferred embodiments of the bionic fiber tactile sensor of the present invention, the IL / PVDF electrolyte layer is obtained by coating a mixed solution containing an ionic liquid on sandpaper provided with a plurality of circular holes, and then peeling it off after drying.
[0014] In some preferred embodiments of the bionic fiber tactile sensor of the present invention, the mass ratio of [EMIM][TFSI], P(VDF-HFP) and DMF in the mixed solution containing the ionic liquid is 5-28:7-8.5:65-85.
[0015] In some preferred embodiments of the bionic fiber tactile sensor of the present invention, the diameter of the circular hole is 3-4 mm.
[0016] Another aspect of the present invention provides a method for preparing an antibacterial, breathable, hydrophobic, self-cleaning bionic fiber tactile sensor, comprising the following steps:
[0017] S1. Preparation of ZIF-67 / Ag NWs / STA fiber electrode layer
[0018] The fiber is placed in a mixed solution of 2-methylimidazole, cobalt nitrate hexahydrate and methanol, and ZIF-67 is loaded on the fiber by an in-situ growth method to obtain ZIF-67 fiber; the Ag NWs solution is coated on both sides of the ZIF-67 fiber, and after drying, the ZIF-67 / Ag NWs fiber is obtained; the stearic acid solution is sprayed on one side of the ZIF-67 / Ag NWs fiber, and after drying, the ZIF-67 / Ag NWs / STA fiber electrode layer is obtained;
[0019] S2. Preparation of IL / PVDF electrolyte layer
[0020] Cut a plurality of circular holes on sandpaper, apply a mixed solution containing ionic liquid on the surface of the sandpaper, dry and peel off to obtain the IL / PVDF electrolyte layer;
[0021] S3. Apply IL / PVDF solution as glue on the two surfaces of the IL / PVDF electrolyte layer prepared in S2, and then adhere the ZIF-67 / Ag NWs / STA fiber electrode layers prepared in S1 on the two surfaces of the IL / PVDF electrolyte layer respectively, and obtain the bionic fiber tactile sensor after drying; wherein the non-hydrophobically modified side of the ZIF-67 / Ag NWs / STA fiber electrode layer faces the IL / PVDF electrolyte layer.
[0022] The ZIF-67 / Ag NWs / STA fiber electrode layer is prepared by placing a fiber with good flexibility in a mixed solution of 2-methylimidazole, cobalt nitrate hexahydrate and methanol, and loading ZIF-67 onto the fiber by an in-situ growth method, which not only retains its inherent fiber structure but also gives it excellent antibacterial properties and micro-nano structure. Then, the Ag NWs solution with high conductivity and antibacterial properties is coated on the ZIF-67 fiber to form a conductive path for the fiber. The cross-linked Ag NWs help to reduce the initial contact area between the electrode and the electrolyte layer, thereby increasing the performance of the sensor (such as sensitivity and detection range) and further increasing the antibacterial properties. After that, the hydrophobic stearic acid STA is sprayed to improve the hydrophobicity and self-cleaning properties of the sensor.
[0023] The IL / PVDF electrolyte layer is obtained by coating a mixed solution containing ionic liquid on the surface of sandpaper treated by a laser cutting machine and then peeling it off through a drying process. This process not only ensures that one side of the electrolyte has a through-hole structure of different levels of height, but also the other side has an octopus suction cup structure, which effectively reduces the initial contact area between the electrode and the electrolyte, thereby improving the sensitivity and resilience of the sensor.
[0024] In some preferred embodiments of the method for preparing a bionic fiber tactile sensor of the present invention, in S1, in the mixed solution of 2-methylimidazole, cobalt nitrate hexahydrate and methanol, the molar ratio of 2-methylimidazole to cobalt nitrate hexahydrate is 2-3:5-15, and the molar concentration of 2-methylimidazole in methanol is 0.25-1 mol / l; the concentration of the Ag NWs solution is 4-7 mg / mL; the mass ratio of STA to water in the stearic acid solution is 1:100-125.
[0025] In some preferred embodiments of the method for preparing a bionic fiber tactile sensor of the present invention, in S2, the mass ratio of [EMIM][TFSI], P(VDF-HFP), and DMF in the mixed solution containing ionic liquid is 5-28:7-8.5:65-85; and the diameter of the circular hole is 3-4 mm.
[0026] On the other hand, the present invention provides an application of an antibacterial, breathable, hydrophobic and self-cleaning bionic fiber tactile sensor, and the application of the bionic fiber tactile sensor in wearable devices and object recognition.
[0027] Compared with the prior art, the bionic fiber tactile sensor and its preparation method and application described in the present invention have the following advantages:
[0028] (1) The bionic fiber tactile sensor described in the present invention starts from three aspects: structural design, material selection and preparation process. By using fiber as a substrate and integrating it with ZIF-67 with a highly stable structure, AgNWs with high conductivity and antibacterial properties, and superhydrophobic stearic acid STA, an electrode layer is obtained; an ionic liquid mixed solution containing rich anions and cations and high stability is used to obtain an electrolyte layer with different microstructures on both sides, one side of which is a combined microstructure of through holes and protrusions, and the other side is an octopus suction cup structure; the prepared bionic fiber tactile sensor has superhydrophobicity and can resist the penetration of the solution, thereby extending its service life and expanding its application range; the self-cleaning performance can reduce the damage to the sensor surface material and effectively remove impurities and other pollutants on the sensor surface; at the same time, the electrode layer and the electrolyte layer have a large number of micropores, allowing the transmission of air / water, providing comfort for long-term wearing; in addition, it also has antibacterial properties to maintain the balance of the skin system; and it has good sensitivity and detection range;
[0029] (2) In the ZIF-67 / Ag NWs / STA fiber electrode layer described in the present invention, a fiber with good flexibility is used in a mixed solution of 2-methylimidazole, cobalt nitrate hexahydrate and methanol, and a highly stable structure of ZIF-67 is loaded onto the fiber by an in-situ growth method. The Ag NWs solution is coated to form a conductive path in the fiber, and the cross-linked Ag NWs help to reduce the initial contact area between the electrode and the electrolyte layer, thereby optimizing the performance of the sensor (such as sensitivity and detection range), while further increasing the antibacterial performance, and then spraying STA stearate with hydrophobic properties to improve the hydrophobicity and self-cleaning performance of the sensor; in addition, the ZIF-67 / Ag NWs / STA fiber electrode layer uses the fiber as the base material, and the subsequent processing does not completely block the micropores of the fiber, so it has excellent air permeability;
[0030] (3) The IL / PVDF electrolyte layer described in the present invention is formed by a mixed solution of ionic liquids rich in anions and cations and with high stability, and has different microstructures on both sides. One side is a combination structure of through holes and protrusions of different heights (since the heights of the particles on the surface of the sandpaper are inconsistent, the protrusions generated are of different heights. At the same time, the gel film is peeled off from the sandpaper. The gel film is relatively thin, and holes of different sizes will be generated after peeling, so there are protrusions and through holes of different heights), and the other side is an octopus suction cup-like structure, which effectively reduces the initial contact area between the electrode and the electrolyte, thereby improving the sensing performance and resilience. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a schematic diagram of the structure of the bionic fiber tactile sensor of the present invention;
[0032] Figure 2 This is a schematic diagram of the working principle of the bionic fiber tactile sensor of the present invention;
[0033] Figure 3 This is an electron microscope image of the ZIF-67 / Ag NWs / STA fiber electrode layer in Example 1 of the present invention;
[0034] Figure 4 This is an electron microscope image of the IL / PVDF electrolyte layer in Example 1 of the present invention;
[0035] Figure 5 middle, Figure 5 a is the sensor response time detection diagram; Figure 5 b is the minimum detection limit diagram of the sensor; Figure 5 c is the sensor stability diagram;
[0036] Figure 6 middle, Figure 6a is a schematic diagram showing the hydrophobicity of the bionic fiber tactile sensor; Figure 6 b is a schematic diagram showing the self-cleaning property of the bionic fiber tactile sensor;
[0037] Figure 7 This is a schematic diagram showing the air permeability of the fiber tactile sensor of the present invention;
[0038] Figure 8 This is a schematic diagram showing the antibacterial property of the fiber tactile sensor of the present invention; wherein, Figure 8 a is the antibacterial photo of Staphylococcus aureus; Figure 8 b is the antibacterial property against Staphylococcus aureus; Figure 8 c is a photo of Staphylococcus aureus; Figure 8 d is the killing rate of Staphylococcus aureus; Figure 8 e is the antibacterial photo of Escherichia coli; Figure 8 f is the antibacterial property against Escherichia coli; Figure 8 g is a photo of Escherichia coli; Figure 8 h is the killing rate of E. coli;
[0039] Fig. 9 This is a schematic diagram of the application of the fiber tactile sensor of the present invention; wherein, Fig. 9 a is a pulse signal monitoring diagram; Fig. 9 b is the monitoring diagram of finger bending action; Fig. 9 c is the elbow bending action detection diagram; Fig. 9 d is the object recognition of the sensor array; Fig. 9 e is the stress distribution of the sensor array.
[0040] Description of Reference Numerals
[0041] 1-IL / PVDF electrolyte, 2-ZIF-67 / Ag NWs / STA fiber electrode layer, 3-ZIF-67, 4-Ag NWs, 5-STA. DETAILED DESCRIPTION
[0042] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.
[0043] The present invention will be described in detail below with reference to the embodiments and the accompanying drawings.
[0044] A method for preparing an antibacterial, breathable, hydrophobic, self-cleaning bionic fiber tactile sensor comprises the following steps:
[0045] S1. Preparation of ZIF-67 / Ag NWs / STA fiber electrode layer
[0046] 1) placing the fiber in a mixed solution of 2-methylimidazole, cobalt nitrate hexahydrate and methanol, and loading ZIF-67 on the fiber by an in-situ growth method to obtain ZIF-67 fiber; wherein, in the mixed solution of 2-methylimidazole, cobalt nitrate hexahydrate and methanol, the molar ratio of 2-methylimidazole to cobalt nitrate hexahydrate is 2-3:5-15, and the molar concentration of 2-methylimidazole in methanol is 0.25-1 mol / l;
[0047] 2) coating the Ag NWs solution with high conductivity and antibacterial properties on both sides of the ZIF-67 fiber, and obtaining the ZIF-67 / Ag NWs fiber after drying; wherein the concentration of the Ag NWs solution is 4-7 mg / mL;
[0048] 3) spraying a stearic acid solution onto one surface of the ZIF-67 / Ag NWs fiber, and obtaining the ZIF-67 / AgNWs / STA fiber electrode layer after drying; wherein the mass ratio of STA to water in the stearic acid solution is 1:100-125;
[0049] S2. Preparation of IL / PVDF electrolyte layer
[0050] A plurality of circular holes with a diameter of 3 to 4 mm are cut on sandpaper using a laser cutter, and then a mixed solution containing an ionic liquid is applied to the surface of the sandpaper, and then the mixed solution containing an ionic liquid is peeled off to obtain the IL / PVDF electrolyte layer; wherein the mass ratio of [EMIM][TFSI], P(VDF-HFP), and DMF in the mixed solution containing an ionic liquid is 5 to 28:7 to 8.5:65 to 85;
[0051] S3. Apply IL / PVDF solution as glue on the two surfaces of the IL / PVDF electrolyte layer prepared in S2, and then adhere the ZIF-67 / Ag NWs / STA fiber electrode layers prepared in S1 on the two surfaces of the IL / PVDF electrolyte layer respectively, and obtain the bionic fiber tactile sensor after drying; wherein the non-hydrophobically modified side of the ZIF-67 / Ag NWs / STA fiber electrode layer faces the IL / PVDF electrolyte layer.
[0052] like Figure 1As shown, the bionic fiber tactile sensor includes an IL / PVDF electrolyte layer 1 located in the middle layer, a ZIF-67 / Ag NWs / STA fiber electrode layer 2 arranged on one side of the IL / PVDF electrolyte layer 1, and a ZIF-67 / Ag NWs / STA fiber electrode layer 2 arranged on the other side of the IL / PVDF electrolyte layer 1; wherein, the IL / PVDF electrolyte layer 1 is loaded with ions, one side is a combined microstructure of through holes and protrusions, and the other side is an octopus suction cup structure; the ZIF-67 / Ag NWs / STA fiber electrode layer 2 is based on fibers, loaded with ZIF-673 of a highly stable structure, and coated on both sides with Ag NWs 4 with high conductivity and antibacterial properties, and then the outward side is hydrophobically modified by superhydrophobic stearic acid STA 5.
[0053] like Figure 2 As shown, the working principle of the bionic fiber tactile sensor is as follows: when pressure is applied to the bionic fiber tactile sensor, the ZIF-67 / Ag NWs / STA fiber electrode layer and the IL / PVDF electrolyte layer will deform under the action of pressure, thereby causing the contact area between the IL / PVDF electrolyte layer and the ZIF-67 / Ag NWs / STA fiber electrode layer to increase and the distance to decrease, causing an increase in capacitance; when the external pressure disappears, the ZIF-67 / Ag NWs / STA fiber electrode layer and the IL / PVDF electrolyte layer will return to their original state, and the capacitance will also return to its original value; the change in capacitance can be converted into an electrical signal and transmitted to the subsequent processing circuit, thereby monitoring the magnitude of the force.
[0054] Example 1
[0055] The preparation of a bionic fiber tactile sensor comprises the following steps:
[0056] S1. Preparation of ZIF-67 / Ag NWs / STA fiber electrode layer
[0057] 1) Mix 25 mL of methanol solution with 0.025 M cobalt nitrate hexahydrate, and then pour a mixed solution of 25 mL of methanol solution and 0.1 M 2-methylimidazole into the above solution; immerse clean fibers in the mixed solution of 2-methylimidazole, cobalt nitrate hexahydrate and methanol, and let stand at room temperature for 48-52 hours; then dry the treated fibers at 60° C. for 30 minutes to obtain ZIF-67 fibers;
[0058] 2) 5 mg / mL Ag NWs dispersion was uniformly sprayed onto ZIF-67 fibers and then dried in an oven at 60 °C for 30 min to obtain ZIF-67 / Ag NWs fibers;
[0059] 3) Under magnetic stirring at 1500 rpm, stearic acid (STA) and hot water were added to a beaker in a mass ratio of 1:125, and stirred in a 1000 rpm magnetic stirring water bath at 70°C for 1 hour to obtain a stearic acid emulsion; the newly prepared stearic acid emulsion was sprayed onto one surface of the ZIF-67 / Ag NWs fiber, and then dried in an oven at 60°C for 30 minutes to obtain a ZIF-67 / Ag NWs / STA fiber electrode layer;
[0060] S2. Preparation of IL / PVDF electrolyte layer
[0061] [EMIM][TFSI], P(VDF-HFP) and DMF were added into a beaker at a weight ratio of 16:7.7:76.3, and then the mouth of the beaker was sealed with plastic wrap to prevent possible evaporation and material exchange with the outside; the IL / PVDF mixed solution was stirred in a magnetic stirring water bath at 60°C for 3 hours until the solution became transparent, indicating that the polymer particles were completely dissolved; a plurality of circular holes with a diameter of 3 mm were cut on sandpaper using a laser cutter, and the spacing between each hole was 4 mm; the IL / PVDF mixed solution was poured onto the sandpaper, and then peeled off after drying in an oven at 60°C for 3 hours to obtain an IL / PVDF electrolyte layer;
[0062] S3. Apply IL / PVDF solution as glue on both surfaces of the IL / PVDF electrolyte layer prepared in S2, and then adhere the ZIF-67 / Ag NWs / STA fiber electrode layers prepared in S1 on both surfaces of the IL / PVDF electrolyte layer, and dry them in an oven at 60°C for 20 minutes to obtain the bionic fiber tactile sensor.
[0063] Example 2
[0064] On the basis of Example 1, the difference from Example 1 is that when preparing the IL / PVDF electrolyte layer, the content of the ionic liquid is different, and [EMIM][TFSI], P(VDF-HFP), and DMF are prepared in a mass ratio of 8:8.3:83.7.
[0065] Example 3
[0066] On the basis of Example 1, the difference from Example 1 is that when preparing the IL / PVDF electrolyte layer, the content of the ionic liquid is different, and [EMIM][TFSI], P(VDF-HFP), and DMF are prepared in a mass ratio of 24:7.1:68.9.
[0067] Comparative Example 1
[0068] On the basis of Example 1, the difference from Example 1 is that when preparing the IL / PVDF electrolyte layer, the content of the ionic liquid is different, and [EMIM][TFSI], P(VDF-HFP), and DMF are prepared in a mass ratio of 32:6.7:61.3.
[0069] Example 4
[0070] On the basis of Example 1, the difference from Example 1 is that when preparing the IL / PVDF electrolyte layer, the diameter of the circular hole cut on the sandpaper by using a laser cutting machine is 4 mm.
[0071] Comparative Example 2
[0072] On the basis of Example 1, the difference from Example 1 is that when preparing the IL / PVDF electrolyte layer, circular holes are not cut, and the ion solution is directly coated on the sandpaper surface.
[0073] Comparative Example 3
[0074] On the basis of Example 1, the difference from Example 1 is that when preparing the IL / PVDF electrolyte layer, the diameter of the circular hole cut on the sandpaper by using a laser cutting machine is 2 mm.
[0075] Sensitivity tests were conducted on Examples 1-3 and Comparative Example 1 to study the effects of different ionic liquid contents in the IL / PVDF fiber electrolyte layer on the sensitivity of the prepared bionic fiber tactile sensor. The data are shown in Table 1.
[0076] Table 1
[0077]
[0078] As shown in Table 1, when the ratio of P(VDF-HFP) / DMF remains unchanged, it means that different proportions of ionic liquid content in the IL / PVDF electrolyte layer will affect the performance of the sensor; as the ionic liquid content increases, the performance of the sensor gradually improves. However, when the ionic liquid content is too high, the IL / PVDF electrolyte will have liquid outflow, and an electrolyte with a breathable solid film cannot be formed.
[0079] Sensitivity tests were conducted on Examples 1 and 4 and Comparative Examples 2 and 3 to study the effect of circular holes of different diameters cut on sandpaper by a laser cutter in the IL / PVDF electrolyte layer on the sensitivity of the prepared bionic fiber tactile sensor. The data are shown in Table 2.
[0080] Table 2
[0081]
[0082] As shown in Table 2, the performance of the sensor (such as sensitivity and detection range) can be improved by using a laser cutter to cut circular holes on sandpaper and introducing an octopus suction cup structure in the IL / PVDF electrolyte layer. However, when the diameter of the circular hole cut by the laser cutter is too large, the octopus suction cup structure of the IL / PVDF electrolyte layer will be too large, resulting in a larger initial contact between the electrolyte layer and the electrode layer, thereby reducing the performance of the sensor. At the same time, if the circular hole size is too small, its performance is not as good as that of a sensor with only one side of the raised microstructure. Therefore, a circular hole of appropriate size is extremely important for improving performance.
[0083] Performance test of the prepared bionic fiber tactile sensor
[0084] 1. As Figure 3 As shown, the electron microscope image of the ZIF-67 / Ag NWs / STA fiber electrode layer prepared in Example 1, the highly stable cubic structure ZIF-67 is loaded into the fiber by the in-situ growth method, which not only retains its inherent fiber structure, but also gives it excellent antibacterial properties and micro-nano structure, and then the highly conductive and antibacterial Ag NWs introduced can make the fiber form a conductive path and increase the antibacterial property, and the introduced super-hydrophobic STA sheet structure can improve the hydrophobicity and self-cleaning performance of the sensor;
[0085] like Figure 4 As shown in the electron microscope image of the IL / PVDF electrolyte layer prepared in Example 1, the front side has a combined microstructure of through holes and protrusions of different heights, and the back side has an octopus suction cup structure, which can effectively reduce the initial contact area between the electrode and the electrolyte, thereby improving the sensitivity; in addition, the octopus suction cup structure can increase the height of the electrolyte layer, making it more resilient.
[0086] 2. If Figure 5 As shown, taking the bionic fiber tactile sensor prepared in Example 1 as an example, the bionic fiber tactile sensor has an ultra-fast response time and recovery time of 100ms and 75ms ( Figure 5 a is the sensor response time detection diagram); it has an ultra-low detection limit of 25Pa ( Figure 5 b is the sensor's minimum detection limit diagram); it has excellent stability, and the reciprocating experiment is basically error-free ( Figure 5 c is the sensor stability diagram).
[0087] 3. Such as Figure 6 As shown, the bionic fiber tactile sensor prepared by the present invention has good hydrophobicity ( Figure 6a is the hydrophobicity diagram of the sensor), the contact angle between the fiber sensor and artificial sweat is 162.5°, the contact angle with beer is 161.8°, the contact angle with juice is 161.8°, the contact angle with tea is 162.3°, the contact angle with water is 164.2°, and the contact angle with milk is 160.4°; the bionic fiber tactile sensor prepared by the present invention has good self-cleaning property, and the vegetable powder on the surface of the sensor can be quickly slid off with the water droplets when the ink is washed. Figure 6 b is the self-cleaning diagram of the sensor).
[0088] 4. Such as Figure 7 As shown, the bionic fiber tactile sensor prepared by the present invention has excellent air permeability. After the sensor is fixed on the head of the hair dryer, air can pass through the sensor to make the dandelion swing.
[0089] 5. As Figure 8 As shown in the figure, the bionic fiber tactile sensor prepared by the present invention has excellent antibacterial properties; the surfaces and surroundings of the fibers, ZIF-67 fibers, ZIF-67 / Ag NWs fibers, and ZIF-67 / Ag NWs / STA fibers are covered with Staphylococcus aureus, and an inhibition zone is formed around the ZIF-67 fibers, ZIF-67 / Ag NWs fibers, and ZIF-67 / Ag NWs / STA fibers after 24 hours; however, in sharp contrast, no inhibition zone is formed around the fibers, indicating that ZIF-67 and AgNWs significantly inhibit bacterial proliferation ( Figure 8 a is the antibacterial photo of Staphylococcus aureus); the synergistic antibacterial effect of ZIF-67 and Ag NWs makes the diameter of the inhibition zone of ZIF-67 / Ag NWs fiber the highest (1.21±0.2mm); however, after spraying STA nanosheets, the antibacterial activity of ZIF-67 / Ag NWs / STA fiber decreased, but it still inhibited bacterial growth ( Figure 8 b is the antibacterial property of Staphylococcus aureus); then, the killing rate of ZIF-67 fiber, ZIF-67 / Ag NWs fiber and ZIF-67 / Ag NWs / STA fiber against Staphylococcus aureus was tested ( Figure 8 c and Figure 8 d is the photo and killing rate of Staphylococcus aureus); ZIF-67 / Ag NWs fibers had the highest killing rate against Staphylococcus aureus (the fewer particles in the field of view, the higher the killing rate); in addition, Escherichia coli was detected on the fibers, ZIF-67 fibers, ZIF-67 / Ag NWs fibers, and ZIF-67 / Ag NWs / STA fibers; an inhibition zone was formed around the ZIF-67 fibers, ZIF-67 / Ag NWs fibers, and ZIF-67 / Ag NWs / STA fibers, among which the inhibition zone around the ZIF-67 / Ag NWs fibers was the largest ( Figure 8 e and Figure 8 f is the antibacterial photo and performance of Escherichia coli); in addition, the killing rate of ZIF-67 fiber is about 46%, the killing rate of ZIF-67 / Ag NWs fiber is about 99%, and the killing rate of ZIF-67 / Ag NWs / STA fiber is about 98% ( Figure 8 g and Figure 8 h is the photo and killing rate of Escherichia coli).
[0090] 6. Such as Fig. 9 As shown, the bionic fiber tactile sensor prepared by the present invention can not only be used as a sensor unit for monitoring human health status and motion detection in daily life ( Fig. 9 a is the pulse signal monitoring diagram, Fig. 9 b is the monitoring diagram of finger bending action. Fig. 9 c is the elbow bending action detection diagram), and can also be used as a sensor array to identify the spatial pressure distribution of human-computer interaction ( Fig. 9 d and 9e show the object recognition and stress distribution of the sensor array).
[0091] The bionic fiber sensor prepared by the present invention has super-hydrophobicity as a whole and can resist the penetration of solutions (such as sweat), thereby extending its service life and expanding its application range; the self-cleaning property can reduce the damage to the surface material of the sensor and effectively remove impurities and other pollutants on the surface of the sensor; at the same time, the electrode layer and the electrolyte layer have a large number of micropores, allowing the transmission of air / water, providing comfort for long-term wearing; in addition, the sensor has antibacterial properties and can maintain the balance of the skin system.
[0092] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. An antibacterial, breathable, hydrophobic, self-cleaning bionic fiber tactile sensor, characterized in that: include: ZIF-67 / Ag NWs / STA fiber electrode layer, wherein the ZIF-67 / Ag NWs / STA fiber electrode layer is based on fiber, loaded with ZIF-67, coated with Ag NWs on both sides, and then hydrophobically modified on one side by STA; An IL / PVDF electrolyte layer, wherein the IL / PVDF electrolyte layer is loaded with ions, one side of the IL / PVDF electrolyte layer is a through-hole and protrusion combination microstructure, and the other side is an octopus suction cup-like structure; There are two ZIF-67 / Ag NWs / STA fiber electrode layers, which are respectively attached to two surfaces of the IL / PVDF electrolyte layer, and the non-hydrophobic modified surface of the ZIF-67 / Ag NWs / STA fiber electrode layer faces the IL / PVDF electrolyte layer.
2. The antibacterial, breathable, hydrophobic, self-cleaning bionic fiber tactile sensor according to claim 1, characterized in that: The ZIF-67 / Ag NWs / STA fiber electrode layer is prepared by loading ZIF-67 on the fiber by an in-situ growth method in a mixed solution of 2-methylimidazole, cobalt nitrate hexahydrate and methanol, coating Ag NWs solution on both sides, drying, and then spraying a hydrophobic STA solution on one side and drying.
3. The antibacterial, breathable, hydrophobic, self-cleaning bionic fiber tactile sensor according to claim 2, characterized in that: In the mixed solution of 2-methylimidazole, cobalt nitrate hexahydrate and methanol, the molar ratio of 2-methylimidazole to cobalt nitrate hexahydrate is 2-3:5-15, and the molar concentration of 2-methylimidazole in methanol is 0.25-1 mol / l; The concentration of the Ag NWs solution is 4-7 mg / mL; The mass ratio of STA to water in the hydrophobic STA solution is 1:100-125.
4. The antibacterial, breathable, hydrophobic, self-cleaning bionic fiber tactile sensor according to claim 1, characterized in that: The IL / PVDF electrolyte layer is obtained by coating a mixed solution containing an ionic liquid on sandpaper provided with a plurality of circular holes, and then peeling off the sandpaper after drying.
5. The antibacterial, breathable, hydrophobic, self-cleaning bionic fiber tactile sensor according to claim 4, characterized in that: The mass ratio of [EMIM][TFSI], P(VDF-HFP) and DMF in the mixed solution containing the ionic liquid is 5-28:7-8.5:65-85.
6. The antibacterial, breathable, hydrophobic, self-cleaning bionic fiber tactile sensor according to claim 4, characterized in that: The diameter of the circular hole is 3-4 mm.
7. A method for preparing an antibacterial, breathable, hydrophobic, self-cleaning bionic fiber tactile sensor, characterized in that: The steps include: S1. Preparation of ZIF-67 / Ag NWs / STA fiber electrode layer The fiber is placed in a mixed solution of 2-methylimidazole, cobalt nitrate hexahydrate and methanol, and ZIF-67 is loaded on the fiber by an in-situ growth method to obtain ZIF-67 fiber; the Ag NWs solution is coated on both sides of the ZIF-67 fiber, and after drying, the ZIF-67 / Ag NWs fiber is obtained; the stearic acid solution is sprayed on one side of the ZIF-67 / Ag NWs fiber, and after drying, the ZIF-67 / Ag NWs / STA fiber electrode layer is obtained; S2. Preparation of IL / PVDF electrolyte layer Cut a plurality of circular holes on sandpaper, apply a mixed solution containing ionic liquid on the surface of the sandpaper, dry and peel off to obtain the IL / PVDF electrolyte layer; S3. Apply IL / PVDF solution as glue on the two surfaces of the IL / PVDF electrolyte layer prepared in S2, and then adhere the ZIF-67 / Ag NWs / STA fiber electrode layers prepared in S1 on the two surfaces of the IL / PVDF electrolyte layer respectively, and obtain the bionic fiber tactile sensor after drying; wherein the non-hydrophobically modified side of the ZIF-67 / Ag NWs / STA fiber electrode layer faces the IL / PVDF electrolyte layer.
8. The method for preparing the antibacterial, breathable, hydrophobic, self-cleaning bionic fiber tactile sensor according to claim 7, characterized in that: In S1, in the mixed solution of 2-methylimidazole, cobalt nitrate hexahydrate and methanol, the molar ratio of 2-methylimidazole to cobalt nitrate hexahydrate is 2-3:5-15, and the molar concentration of 2-methylimidazole in methanol is 0.25-1 mol / l; the concentration of the Ag NWs solution is 4-7 mg / mL; and the mass ratio of STA to water in the stearic acid solution is 1:100-125.
9. The method for preparing the antibacterial, breathable, hydrophobic, self-cleaning bionic fiber tactile sensor according to claim 7, characterized in that: In the S2, the mass ratio of [EMIM][TFSI], P(VDF-HFP), and DMF in the mixed solution containing ionic liquid is 5-28:7-8.5:65-85; and the diameter of the circular hole is 3-4 mm.
10. Use of the antibacterial, breathable, hydrophobic, self-cleaning bionic fiber tactile sensor according to any one of claims 1 to 6, or the antibacterial, breathable, hydrophobic, self-cleaning bionic fiber tactile sensor prepared by the preparation method according to any one of claims 7 to 9, characterized in that: The bionic fiber tactile sensor is used in wearable devices and object recognition.
Citation Information
Patent Citations
Piezoelectric tactile sensor based on human skin bionics principle
CN108489643A
Flexible breathable high-sensitivity tactile sensor and preparation and application thereof
CN116337284A
Bionic tactile sensor, preparation method and application thereof
CN116465522A
Fiber tactile sensor, preparation method and application thereof
CN117367631A
Sweat absorption and discharge nanofiber film and nanofiber-based flexible touch-temperature sensor
CN117926576A